FACTORS ASSOCIATED WITH TREATMENT NON-ADHERENCE AMONG TUBERCULOSIS PATIENTS IN THE FREE HEALTHCARE PROGRAM AT BARANTI PUBLIC HEALTH CENTER - Sulfa; Pratiwi Ramlan; Khaeriyah Adri; Sunandar Said (CV. Fahr Publishing, 2026)
This study examined factors associated with treatment non-adherence among tuberculosis (TB) patients enrolled in the free healthcare program at Baranti Public Health Center, Sidenreng Rappang Regency, Indonesia. A quantitative cross-sectional design was used, and all 30 eligible TB patients undergoing treatment during the study period were recruited through total sampling. Data were collected using structured questionnaires assessing knowledge, motivation, perceived barriers, family support, access to healthcare services, and treatment adherence. Univariate statistics were used to summarize the data, while Chi-Square or Fisher’s exact tests were applied as appropriate, with statistical significance set at p < 0.05. Fourteen respondents (46.7%) were classified as non-adherent. Perceived barriers were significantly associated with treatment non-adherence (p = 0.021), whereas knowledge (p = 0.156), motivation (p = 0.232), family support (p = 0.452), and access to healthcare services (p = 0.153) were not statistically significant. The novel contribution of this study is the simultaneous assessment of individual, family, service-access, and perceived-barrier factors in a free-treatment setting, where direct medication costs have already been removed. The findings indicate that residual treatment-related barriers remain relevant and should be addressed through patient-centered counseling, early management of medication-related problems, continuous follow-up, and practical support at the primary healthcare level.